A prickly puzzle: phylogeny and evolution of the Carduus-Cirsium group (Cardueae: Compositae), and untangling the taxonomy of Cirsium in North America - Ackerfield, Jennifer R., author; Simmons, Mark, advisor; Kondratieff, Boris, committee member; Smith, Melinda, committee member; Steingraeber, David, committee member; Funk, Vicki, committee member (Colorado State University. Libraries, 2020)
Generic delimitations within the cosmopolitan Carduus-Cirsium group (i.e., "thistles") have a long history of taxonomic confusion and debate. We present the most comprehensive molecular phylogeny of the group to date to test generic limits, reconstruct the evolution of pappus type, and elucidate the role of chromosomal evolution. We offer two solutions for the recognition of monophyletic genera: (1) consolidate all taxa into one large genus (Carduus or Cirsium), or (2) recognize each major clade as a genus (Carduus, Cirsium, Eriolepis, Notobasis, Picnomon, Silybum, and Tyrimnus). Under the second proposal, the cryptic genus Eriolepis is segregated from Cirsium, and the African Carduus are included within Cirsium. The best diagnosable morphological character to delimit the genera is pollen type, which is not practical in field-based application. We caution that prior to implementing either solution, a thorough, comprehensive morphological analysis of all current members of Cirsium sect. Epitrachys (= genus Eriolepis) be completed. Future morphological studies may find additional achene or leaf surface characters that could be used for practical field identification of the segregate genera. The data show that the plumose pappus state is symplesiomorphic for the group, with one transition to barbellate pappus, likely followed by a reversal to its ancestral state as the group colonized Eurasia. The data are consistent with a North African origin in the region of the Mediterranean and a single colonization event to North America. An ancestral chromosome state of n = 17 is hypothesized for the group, and a descending dysploidy series in Carduus is hypothesized to correspond with the aridification of the Mediterranean region. The Carduus-Cirsium group highlights the difficulty of delimiting morphologically similar, cryptic genera. Cirsium is one of the most taxonomically challenging groups of Compositae in North America. This study represents the first attempt to infer a broadly sampled phylogeny of Cirsium in North America. The two main objectives are to: (1) test whether currently hypothesized species variety complexes (C. arizonicum, C. clavatum, C. eatonii, and C. scariosum) constitute monophyletic lineages, and (2) recircumscribe any taxa that are identified as problematic. Phylogeny reconstructions based on DNA sequence data from two nuclear ribosomal regions and four plastid markers were used to infer evolutionary lineages and test species' delimitations. Eight species varietal complexes were resolved as polyphyletic. We recircumscribed these complexes and in doing so found evidence to support the recognition of six new taxa. We hypothesize that the extensive taxonomic difficulty within Cirsium is the result of several factors: 1) previously undescribed taxa, 2) inadequate representation of taxa from herbarium specimens, 3) phenotypic convergence, 4) hybridization, and 5) incipient speciation. While we can provide evidence to support the recircumscription of some taxa, others remain unresolved.
Keywords: Cirsium; thistles; taxonomic delimitations; Asteraceae